Pemaparan dalam Kegiatan Focus Group Discussion; Analisis Jabatan dan Manfaatnya bagi Organisasi Pemerintah - muafi muafi (UII, 2018)
Job analysis has the main function to improve the organizational performance the individual in the organization. The implementation of job analysis can help employee to understand the job that are and will be occupied. Organization will have simplicity to place their employee who is suitable with the competency, which is the right man in the right place. This community service is done by doing material exposure and Focus Group Discussion (FGD) with the articipant that is attended by government officials on the Regency of Hulu Sungai Tengah, South Borneo. Knowledge and data that is conducted from the method and job analysis procedure on FGD can be useful as a basis of every practice and other human resource management activities, such as performance evaluation and compensation in government organization. It is also used as advice in job designing and redesigning.